Estimating Residents’ Behaviour Model in Disposing of Waste in the Cisadane River: Model Penduga Perilaku Warga Membuang Sampah di Sungai Cisadane - Andhy Rahmat Padyawan; Ario Damar; Sigid Hariyadi; Taryono Taryono (Jurnal Pengelolaan Perikanan Tropis (Journal of Tropical Fisheries Management), 2021)
Binary logit regression analysis is to determine the probability that describes the relationship between a response variable and a predictor variable. This analysis is based on the logistic distribution and is used to model the relationship between the response variables and the explanatory variables. This study aims to analyze the decision factors of residents who live on the Cisadane river border on the possibility of dumping waste directly into the river and not throwing garbage into the river (burned, buried in the ground and dumped into the TPS). The results of testing the logistic regression model using SPSS Statistics version 25 software obtained 5 predictive variables with the selection of the best model where the availability of TPS, number of TPS, garbage officers, the role of community leaders and the impact of river waste had a significant effect on the decision factors of residents to throw garbage into the Cisadane river.